PENGARUH SIKAP GURU PADA PROFESI DAN PENGEMBANGAN DIRI TERHADAP KOMPETENSI PROFESIONAL GURU KIMIA DI KABUPATEN BENGKULU SELATAN DAN KAUR TAHUN 2020 - Heldah Pariana; Zakaria Zakaria (Manajer Pendididikan, 2020)
ABSTRACT This research is a quantitative study which aims to determine the effect of thunder in the profession on the professional competence of chemistry teachers, the influence of self-development on the professional competence of chemistry teachers and the influence of teacher attitudes on the profession and self-development on the professional competence of chemistry teachers. The method used is descriptive quantitative method using simple regression analysis and multiple regression. The results of this study are that there is a positive and significant influence both partially and jointly between the independent variables, namely teacher attitudes towards the profession and self-development on the professional competence of chemistry teachers. Keywords: Attitudes of teachers to the profession, Self-development and Professional Competence of Chemistry Teachers